Ocorrência da brucelose e tuberculose bovina e percepção de riscos de produtores de leite do município de Paranaíba, Mato Grosso do Sul: Gilson Luiz Piva Filho. - - Piva Filho, Gilson Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Brucellosis and Bovine Tuberculosis are zoonoses worldwide distribution, relevant to the economy and public health. In order to evaluate the occurrence of these diseases in a sample of dairy cattle herd in the municipality of Paranaiba, MS, Brazil, as well as the perception of dairy farmers on the risk of these diseases to livestock and public health, 42 properties were visited and applied a questionnaire to detect failures in health management that could be associated with the occurrence of these diseases. It was collected blood samples of 20% (378) lactating cows from a total of 1.889, which were subjected to screening, with Rose-Bengal Test (RBT) and positives confirmed by the reactants test 2-Mercaptoethanol (2-ME) for brucellosis. Tuberculosis was tested by the Cervical Test Simple (CTS) for screening and Comparative Cervical Test (CCT) as confirmatory results were inconclusive. The occurrence of both brucellosis and tuberculosis on the properties was 2.4% (1/42). Of the properties, 26.2 % (11/42) milk intended for informal sale, only 7.1% (03/42) of owners recognized milk as food capable of transmitting zoonosis; 83.3% (35/42) are unaware of the National Program for Control and Eradication of Brucellosis and Tuberculosis and never underwent tests in animals and 81% (34/42) does not have a quarantine paddock on the property. The data showed deficiency in risk perception. Integrate health education in the control of brucellosis and tuberculosis contribute to the milk producers to adopt measures that will mitigate the risks to animal and human health
Keywords: Tuberculose em bovino; Educação sanitária; Epidemiologia veterinaria; Zoonoses; Brucelose em bovino; Percepção do risco; Bovine brucellosis